A Case Study on Student Hostel Products Online Resale and Exchange with Less Space and Time Complexities - Sai Bhaskar Reddy S, Monish S, Varma K.S.V.S.V, Pradeep, Gopichand G (International Journal of Advanced Science and Technology, 2020)
Nowadays, the students of colleges are facing a lot of challenges in managing and saving their money, so we are trying to make a database where we focus on this problem of the students. In this paper, we had given a case study on such a real-life example, As the new academic year starts almost all the students are allotted a new hostel block and there is a high possibility that the previous block’s bed size would not be same as of the new one and hence their mattresses won’t fit in the bed. Thus, at this point of time our database would come in use to the students where they can sell or exchange their mattresses. Like this there will be a lot of items which the students don’t want or want to exchanges so they will have to just contact us and we fill display their items or products for sale or exchange. The students can also visit our website to know about the products which are on sale or exchange see the product’s specifications and contact the seller to buy or exchange both simultaneously and efficiently by using various data structures and with a relatively less time and space complexity.